REPRESENTASI KEKERASAN DALAM NOVEL LAUT BERCERITA KARYA LEILA S. CHUDORI (REPRESENTATION OF VIOLENCE IN LAUT BERCERITA NOVEL BY LEILA S. CHUDORI) - Yulina Rahmi (Universitas Lambung Mangkurat, 2021)
AbstractRepresentation of Violence in Laut Bercerita Novel by Leila S. Chudori. This study aims to describe the forms of violence and resistance in the novel Laut Bercerita by Leila S. Chudori. The description is done by discourse analysis. Critical discourse analysis examines various social forms and their imbalances displayed through text, then relates them to social and political contexts. This research uses descriptive qualitative method with Norman Fairclough's critical discourse analysis approach Based on the analysis, there are three types of violence, namely physical, verbal, and bureaucratic violence. The form of physical violence are beatings and torture. The form of verbal violence are to accuse and ridicule. Bureaucratic violence is shown in the form of a prohibition on joining a formal institution for people with a certain background and the prohibition of staging theater or poetry which are considered to carry certain ideologies. Meanwhile, there are two types of resistance representations, namely open resistance and closed resistance. Open resistance is shown in the form of demonstrations. Closed resistance is shown in the form of resistance to categories imposed on society. Key words: discourse practice, violence, representation AbstrakRepresentasi Kekerasan dalam Novel Laut Bercerita Karya Leila S. Chudori. Penelitian ini bertujuan untuk mendeskripsikan wujud kekerasan dan perlawanan dalam novel Laut Bercerita karya Leila S. Chudori. Deskripsi tersebut dilakukan dengan analisis wacana. Analisis wacana kritis mengkaji beragam bentuk sosial dan ketimpangannya yang ditampilkan melalui teks, kemudian menghubungkannya dengan konteks sosial dan politik. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan analisis wacana kritis Norman Fairclough. Berdasarkan hasil analisis, terdapat tiga jenis kekerasan, yaitu kekerasan fisik, verbal, dan birokratik. Kekerasan fisik dengan wujud pemukulan dan penganiayaan. Kekerasan verbal dengan wujud menuduh dan mengejek. Kekerasan birokratik ditunjukkan dalam wujud larangan bergabung dengan suatu institusi formal bagi orang dengan latar belakang tertentu dan larangan pementasan seni teater atau puisi yang dianggap membawa ideologi tertentu. Sedangkan, representasi perlawanan terdapat dua jenis, yaitu perlawanan terbuka dan perlawanan tertutup. Perlawanan terbuka ditunjukkan dalam wujud demonstrasi. Perlawanan tertutup yang ditunjukkan dalam bentuk penolakan terhadap kategori-kategori yang dipaksakan terhadap masyarakat. Kata-kata kunci: wacana kritis, kekerasan, representasi